Design, Synthesis, and Antioxidant and Anti-Tyrosinase Activities of (Z)-5-Benzylidene-2-(naphthalen-1-ylamino)thiazol-4(5H)-one Analogs: In Vitro and In Vivo Insights - Hee Jin Jung; Hye Jin Kim; Hyeon Seo Park; Hye Soo Park; Jeongin Ko; Dahye Yoon; Yujin Park; Pusoon Chun; Hae Young Chung; Hyung Ryong Moon (Molecules)
Fifteen compounds (1–15) constructed on a hybrid structure combining a β-phenyl-α,β-unsaturated carbonyl template and a 2-aminothiazol-4(5H)-one scaffold were designed and synthesized as potential novel anti-tyrosinase substances. Two compounds (10 and 15) showed more potent inhibition against mushroom tyrosinase than kojic acid, and the inhibitory activity of 10 (IC50 value: 1.60 μM) was 11 times stronger than that of kojic acid. Lineweaver–Burk plots indicated that these two compounds were competitive inhibitors that bound to the mushroom tyrosinase active site, which was supported by in silico experiments. Compound 10 was an anti-tyrosinase and anti-melanogenic substance in B16F10 cells and was more potent than kojic acid, without cytotoxicity. Compound 15 exhibited the most potent effect on zebrafish larval depigmentation and showed a depigmentation effect comparable to kojic acid, even at a concentration 200 times lower. Compounds 8 and 10 exhibited strong antioxidant capacities, scavenging 2,2-diphenyl-1-picrylhydrazyl, (2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid)+ radicals, and reactive oxygen species. Hybrid compounds 10 and 15 are potential therapeutic agents for skin hyperpigmentation disorders.